1996
DOI: 10.1002/(sici)1097-4652(199604)167:1<173::aid-jcp20>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activities affecting exogenous nicotinamide adenine dinucleotide in human skin fibroblasts

Abstract: The fate of nicotinamide adenine dinucleotide (NAD), AMP, and ADP-ribose supplied to intact human skin fibroblasts was monitored, and the concentrations of intra- and extracellular pyridine and purine compounds were determined by HPLC analysis. Two enzymatic activities affecting extracellular NAD were detected on the plasma membrane, one hydrolyzing the pyrophosphoric bond and yielding nicotinamide mononucleotide (nucleotide pyrophosphatase) and the other cleaving the glycoside link and releasing nicotinamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In a previous study, we demonstrated that NAD‐glycohydrolase (cleaving NAD into nicotinamide and ADPR), nucleotide pyrophosphatase (cleaving NAD into NMN and AMP), and 5′‐nucleotidase are the enzymes involved in extracellular NAD catabolism in human skin fibroblasts. We also showed that the final products of the extracellular NAD metabolism are nicotinamide, NMN, hypoxanthine and adenine [Aleo et al, 1996]. In the present study, we investigated the metabolic fate of the extracellular NAD purine moiety, showing that adenosine is the form which permeates the cell membrane.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In a previous study, we demonstrated that NAD‐glycohydrolase (cleaving NAD into nicotinamide and ADPR), nucleotide pyrophosphatase (cleaving NAD into NMN and AMP), and 5′‐nucleotidase are the enzymes involved in extracellular NAD catabolism in human skin fibroblasts. We also showed that the final products of the extracellular NAD metabolism are nicotinamide, NMN, hypoxanthine and adenine [Aleo et al, 1996]. In the present study, we investigated the metabolic fate of the extracellular NAD purine moiety, showing that adenosine is the form which permeates the cell membrane.…”
Section: Discussionmentioning
confidence: 66%
“…In a previous report [Aleo et al, 1996], we demonstrated that NAD‐glycohydrolase, nucleotide pyrophosphatase and 5′‐nucleotidase are located on the outer surface of human skin fibroblasts. Nucleotide pyrophosphatase cleaves NAD to nicotinamide mononucleotide and AMP, and 5′‐nucleotidase hydrolyses AMP to adenosine.…”
mentioning
confidence: 51%
See 2 more Smart Citations